Evaluating four neutron-gamma discrimination methods with EJ-301 scintillator - Phan, Văn Chuân (Springer Nature, 2023)
The penetration of gamma in neutron spectra reduces the accuracy of measurement results, especially when using the scintillation detector. The digital method can be used to identify either neutron or gamma pulses. In order to select the algorithm for detector using EJ-301 liquid scintillator (EJ-301 detector), the Matlab Simulink tool was used to simulate neutron counting system. The results show that the figure of merits (FoM) of threshold crossing time (TCT), pulsed gradient analysis (PGA), charge comparison (CC), and correlation pattern recognition (CPR) methods for the energy threshold 50 keVee (keV electron equivalent) are 1.1, 0.84, 2.34 and 1.04, respectively. An experiment was conducted with prototype EJ-301 detector and the DRS4 digitizer to validate simulation results.